Uk, Commonwealth and common market : a reappraisal - Meade, James E.; Johnson, Harry G. (Westminster : The Institute of Economic Affairs, 1970)
The purpose of the papers is to contribute a stream of authoritative, objective and readable commentary to the shaping of economic opinion and policy
osc 16/01/2019
Loans
Keywords: International Economic relations; United Kingdom; Commonwealth